2016
DOI: 10.1245/s10434-016-5267-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there an Ideal Breast Conservation Rate for the Treatment of Breast Cancer?

Abstract: Since the results of randomised controlled trials in the last quarter of the twentieth century were reported, it has been conventionally accepted that breast conservation treatment (BCT) provides equivalent survival to mastectomy for early breast cancer. As expected, there was an initial fall in the use of mastectomy. The first decade of the twenty-first century, however, witnessed a trend of increasing mastectomy rates in some regions. This perplexing circumstance served as an impetus for a relook at survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…Lastly, while mastectomy rates are decreasing, at 49%, they are still too high compared to a breast conservation goal of at least 70% [25]. Breast conservation surgery and mastectomy have equivalent survival rates (16), and with OS techniques, locoregional recurrence rates may also show no statistical difference when compared to mastectomy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, while mastectomy rates are decreasing, at 49%, they are still too high compared to a breast conservation goal of at least 70% [25]. Breast conservation surgery and mastectomy have equivalent survival rates (16), and with OS techniques, locoregional recurrence rates may also show no statistical difference when compared to mastectomy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al. concur that a threshold of 70% best represents the evidence [ 25 ] and this corresponds with ESMO guidelines [ 28 ]. Our finding of an overall 64% of the membership achieves that BCS rate (see Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Multiple prospective randomised trials over the past decades have demonstrated that patient survival after undergoing breast conserving surgery (BCS) is equivalent to mastectomy in the treatment of invasive breast cancer [ [23] , [24] , [25] ]. Internationally the breast conservation rate has been used to compare cancer care among various geographical areas and centres, race or socioeconomic status, fellowship-trained versus general surgeons etc [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…1012,26 Simultaneous oncological and reconstructive comprehensive information leads to high rates of reconstruction and presumably reduces suboptimal, from the oncological or plastic surgery standpoint, patient decisions. 8,11,12,17,27,28 However, patient's metachronous exposure to reconstructive approaches and education, providing the patient some time for reflection and extra education, results in a significant rate of at least “second thoughts” or frankly for requests of changes in the preliminary oncological plan. Possibly, education on the aesthetic outcomes, balanced information on the pitfalls of different procedures, and repeated exposure of the patient to the oncological perspective, as a geographically and timely separate encounter with another surgical consultant, all contribute to a significant rate of changes or consideration of changes.…”
Section: Discussionmentioning
confidence: 99%